IDENTIFIKASI SENYAWA BIOAKTIF MADU DI BEBERAPA DAERAH SUMBAWA DENGAN MENGGUNAKAN GAS CHROMATOGRAPHY - dinar saputri; Yolli Putri (Faculty of Agriculture Science & Technology, 2020)
Sumbawa forest honey is one of the featured products in Sumbawa, which is believed to have many health effects. Forest honey on Sumbawa island is mostly produced by Apis dorsata bees. This research used Sumbawa honey from Batu Lanteh, Punik, Lape and Moyo Island areas. The bioactive compounds of honey samples were extracted by using dispersive liquid-liquid microextraction method. Furthermore, bioactive compounds were identified using Gas Chromatography Mass Spectromethry (GC MS). From the chromatogram results, it was found that several siloxane compounds might be formed because there was an error in the RTx-5Ms column in which there was silica. In addition, compounds that have antioxidant and anti-microbial effects are also identified such as, heptadecene-(8)-carbonic acid, 2,3-Dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one, 9-octadecanoic acid, 7,9-di-tert-butyl-1-oxaspiro[4.5]deca-6,9-diene-2,8-dione, hexadecanoic acid dan 7,9-di-tert-butyl-1-oxaspiro[4.5]deca-6,9-diene-2,8-dione. Hydroxymethyl furfural or compounds that are formed by heating or overlong storage and are an indicator of food damage were also identified in this study.